2023
DOI: 10.1186/s12969-023-00841-8
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging visual outcomes in children with idiopathic and JIA associated uveitis: a population-based study

Abstract: Background Pediatric uveitis is typically asymptomatic and may become chronic affecting ocular structures and vision. We evaluated visual outcomes, clinical features, medication, and uveitis activity in children with either idiopathic uveitis (idio-U) or juvenile idiopathic arthritis associated uveitis (JIA-U). Methods A longitudinal, population-based cohort study of children with uveitis in 2008–2017. The data included parameters for age, gender, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Notably, DSCIC greatly increases the risk of JIA, which was consistent with the clinical observation of uveitis with JIA concomitant ( 14 , 55 , 56 ). Siiskone found in a cohort study that 99% of JIA-associated uveitis was concentrated in the anterior ( 14 ). JIA and childhood uveitis are very difficult to diagnose and may have serious clinical consequences.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Notably, DSCIC greatly increases the risk of JIA, which was consistent with the clinical observation of uveitis with JIA concomitant ( 14 , 55 , 56 ). Siiskone found in a cohort study that 99% of JIA-associated uveitis was concentrated in the anterior ( 14 ). JIA and childhood uveitis are very difficult to diagnose and may have serious clinical consequences.…”
Section: Discussionsupporting
confidence: 85%
“…Reports have suggested that 33.2% of people with AS, 7% of those with PsA, and 25%–39% of RA patients might develop corresponding eye disorders, which would further lead to serious consequences such as loss of vision or even blindness ( 10 13 ). Furthermore, it is worth noting that a substantial portion of pediatric uveitis cases are linked to JIA ( 14 16 ). A strong relationship between inflammatory arthritis and eye diseases has been investigated in several observational studies, encompassing multiple sites like the uvea, retina, sclera, and cornea ( 10 , 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…These numbers are much bigger than noted in our population-based cohort. One explanation for this discrepancy might be the implementation of modern and more e cient treatment of uveitis especially for children with JIA-U in Finland during the last two decades (9). Female gender was over-represented in ocular complications among the participants of the present study: 73% of patients with glaucoma, 71% with ocular hypertension, and 52% of those with cataract were girls.…”
Section: Discussionmentioning
confidence: 60%
“…JIA onset after the age of 5 years, no use of corticosteroids, and use of adalimumab treatment has been shown to be associated with uveitis inactivity for at least 6 months (8). Modern treatment modalities of uveitis have improved the visual prognosis of pediatric uveitis (9,10). The long-term impact of modern medications including diseasemodifying antirheumatic drugs (DMARDs) and biologic therapy (bDMARDs) on frequency and severity of uveitis complications in children is not fully established.…”
Section: Introductionmentioning
confidence: 99%
“…4,21,22 Treatment with long-term immunosuppressive medications has improved visual outcomes over time. 5,[23][24][25] More recent population-based cohort studies of JIA uveitis children from the Nordic region and the Netherlands demonstrate blindness rates as low as 2% to 3.8%, as measured by visual acuity at last follow-up. 5,25 The earlier introduction of systemic immunomodulatory treatment is theorized to be a key factor for improved visual prognoses.…”
Section: Discussionmentioning
confidence: 99%